2014
DOI: 10.1186/2046-4053-3-59
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathy for allergic rhinitis: protocol for a systematic review

Abstract: BackgroundAllergic rhinitis is a global health problem that is often treated with homeopathy. The objective of this review will be to evaluate the effectiveness of homeopathic treatment of allergic rhinitis.Methods/DesignThe authors will conduct a systematic review. We will search Medline, CENTRAL, CINAHL, EMBASE, AMED, CAM-Quest, Google Scholar and reference lists of identified studies up to December 2013.The review will include randomized controlled trials that evaluate homeopathic treatment of allergic rhin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The methods have been clearly stated in the previously published protocol. 28 A prospective protocol was first published in PROSPERO (CRD42013006741).…”
Section: Methodsmentioning
confidence: 99%
“…The methods have been clearly stated in the previously published protocol. 28 A prospective protocol was first published in PROSPERO (CRD42013006741).…”
Section: Methodsmentioning
confidence: 99%
“…In seasonal AR, symptoms occur during exposure to seasonal allergens such as pollen, while in the case of perennial AR, symptoms may last for 2 hours a day and more than 9 months a year. Symptoms in episodic rhinitis occur due to exposure to allergens which are not normally present, including allergens from cats and other pets [2]. Symptoms of AR usually appear before the age of 20, and the bothersome nature of AR symptoms can severely effect daily activities including work performance [3] , examination performance [4] and psychosocial well being [5].…”
Section: Introductionmentioning
confidence: 99%
“…9 Clinical prescription aims at treating the disorder using symptoms of the ailment. 10 For example, local symptoms of allergy are looked at and a remedy is prescribed. 6 Constitutional prescription aims to bolster the entire constitution of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…7 While constitutional prescription uses a single remedy, complex prescription involves using two or more remedies. 10 Reilly et al reported evidence showing improvement with homeopathy over placebo in patients with hay fever, asthma and perennial rhinitis, using principal inhalant allergen (isopathy). 9 Taylor et al conducted an overview and pooled analysis of the four trials and showed clear benefit with the homeopathic intervention as compared to the placebo.…”
Section: Introductionmentioning
confidence: 99%